The intonation of wh- questions in a language contact situation: the case of Galician and Galician Spanish bilingual speakers - Rosalía Rodríguez Vázquez (Estudios de Fonética Experimental)
Although language contact is one of the driving forces of language change at any level, little is known about how intonational change may be induced by language contact. This article describes the intonational consequences of the contact between Galician and Spanish. In order to achieve this goal, a corpus comprising 546 Wh- questions collected by means of the Discourse Completion Task is analysed. The data obtained from bilingual speakers show that the intonation patterns of Wh- questions in Galician Spanish are the same as in Galician, while they differ from the intonation patterns of Wh- questions in the other documented varieties of Peninsular Spanish (Central Peninsular Spanish, Manchego, Andalusian, Cantabrian, Asturian and Leonese Spanish). This suggests that there exists a direct intonational transfer phenomenon from Galician to the variety of Spanish spoken by bilingual speakers in Galicia.